mLearning: an innovative conceptualization to expand Education for everyone, anytime, everywhere - Dissanayake, Lakshman (Sprouts, 2009)
This paper conceptualizes how mLearning methodology can be used to provide high quality education for those who are unable to be present regularly in educational institution due to various reasons. The innovative approach to mLearning methodology proposed here is unique because this method has incorporated everything that a student will expect from an educational institution about his education and also what a teacher expects from his students. In addition, this method also has integrated all the elements that ...
Keywords: mLearning: an innovative conceptualization to expand Education for everyone, anytime, everywhere